2017
DOI: 10.2903/sp.efsa.2017.en-1282
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of primary introduction of highly pathogenic and low pathogenic avian influenza virus into European poultry holdings, considering at least material contaminated by wild birds and contact with wild birds

Abstract: Avian influenza (AI) is a constant threat to the poultry industry in Europe. Up to date assessments of the factors influencing the probability of introduction of infection into poultry holdings are required for the implementation of informed prevention and control measures. We carried out a systematic literature review to identify and synthesise the evidence on risk factors of AI introduction into European poultry holdings. A review protocol was built, which considered the electronic search strategy, criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Among gallinaceous poultry categories, free-range laying hens was the poultry category with the highest seropositive percentage (0.5%), although still much lower than the percentages observed in aquatic poultry. It has been shown that outdoor access of laying hens, which increases the risk of direct or indirect exposure to wild birds and the AI viruses they shed, may explain the high frequency of detection of AI antibodies in this poultry category (Bouwstra et al, 2017;CVI et al, 2017). No H5 or H7 detections occurred in 2018 in turkeys, although, the largest number of non H5/H7 seropositive establishments among the gallinaceous categories (not including gallinaceous game birds) were found in fattening turkeys (n = 20).…”
Section: Poultrymentioning
confidence: 99%
See 1 more Smart Citation
“…Among gallinaceous poultry categories, free-range laying hens was the poultry category with the highest seropositive percentage (0.5%), although still much lower than the percentages observed in aquatic poultry. It has been shown that outdoor access of laying hens, which increases the risk of direct or indirect exposure to wild birds and the AI viruses they shed, may explain the high frequency of detection of AI antibodies in this poultry category (Bouwstra et al, 2017;CVI et al, 2017). No H5 or H7 detections occurred in 2018 in turkeys, although, the largest number of non H5/H7 seropositive establishments among the gallinaceous categories (not including gallinaceous game birds) were found in fattening turkeys (n = 20).…”
Section: Poultrymentioning
confidence: 99%
“…Wild birds of the orders Anseriformes and Charadriiformes are considered major reservoirs for LPAI viruses; during the last years, wild birds have been also implicated in the intercontinental spread of H5 HPAI viruses (The Global Consortium for H5N8 and Related Influenza Viruses, 2016). Hence, wild birds are considered the main source of introduction of AIV infections in poultry in Europe (CVI et al, 2017). To implement appropriate measures to prevent incursions, or to control the spread of the disease when incursions occur, Member States (MSs) have implemented surveillance programmes in poultry and wild birds.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the weighting of risk factors would be based on quantitative scientific evidence (Bouwstra et al, 2017;Gonzales et al, 2017), however as indicated in the 2017 EFSA opinion, such evidence is sparse across Europe. In 2016, the Annual Report on surveillance for AI in poultry and in wild birds in Member States of the European Union showed that 10/28 MSs performed risk based surveillance (Animal and Plant Health Agency, 2017).…”
Section: Desirablementioning
confidence: 99%
“…Further scientific evidence is provided in the systematic literature review performed by the AI consortium, identifying and synthesising the evidence on risk factors of HPAI and LPAI introductions into European poultry holdings (data received as per procurement, Linnaeus University (SE), Erasmus Medical Centre (NL), OC/EFSA/ALPHA2015/01 supplemented with NP/EFSA/ALPHA/2015/04, Gonzales et al, 2017).…”
Section: Regression Coefficient Probability Hpaiv Infection Worst-cas...mentioning
confidence: 99%